A Case Report of Two Kala-Azar Cases in China Diagnosed by Metagenomic Next-Generation Sequencing - Gao, Hongguang; Wang, Jing; Zhang, Shu; Li, Tian (Frontiers in Microbiology, 2022)
Background Leishmaniasis being a local disease, as kala-azar this particular form is a visceral form. It is transmitted by sandflies, and is a parasitic disease involving the reticuloendothelial system of mononuclear macrophages. Due to its poor prognosis and high fatality rate, the fatality rate of patients without effective treatment can exceed 95%. Thereby, early diagnosis and treatment can significantly improve its prognosis. The metagenomic next-generation sequencing (mNGS) has the advantage of being able to find pathogens that cannot be detected by traditional methods. More importantly, it can conduct nucleic acid detection of pathogens covering a wide range in a short time. For infectious diseases like kala-azar, which is clinically complicated and difficult, mNGS detection provides a basis for accurate etiological diagnosis. Case Report We report 2 cases of kala-azar in West China Hospital, Chengdu, China. The first case is a 47-year-old male patient who had recurrent fever for 4 months, accompanied by reduction of red blood cell, white blood cell, and blood platelet. He was detected by mNGS and clinically diagnosed as kala-azar (Leishmania detection), finally died of multiple organ failure. The second patient was a 15-year-old male who had fever for more than 10 days. He was detected by mNGS and clinically diagnosed as kala-azar (Leishmania detection). He recovered and discharged quickly after treatment with sodium stibogluconate. Conclusion Efforts should be made to improve early etiological diagnosis in order to improve patient prognosis. mNGS detection is beneficial to the diagnosis and treatment of infectious diseases with unknown causes in the early stage of emergency treatment.